2003
DOI: 10.1046/j.1439-0523.2003.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in melon based on microsatellite variation

Abstract: A set of 18 simple‐sequence repeat (SSR or microsatellite) markers was used to study genetic diversity in a collection of 27 melon (Cucumis melo L.) accessions, representing a broad range of wild and cultivated melons. The materials studied were highly polymorphic for SSRs and a total of 114 alleles were detected (average of 6.3 alleles per locus). Cluster analysis suggests the division of these accessions into two major groups, largely corresponding to the division of C. melo in the two subspecies agrestis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
85
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 29 publications
16
85
2
1
Order By: Relevance
“…The mean number of allele and effective alleles for SSR loci for the 24 Iranian accessions were 4.11 and 2.38, respectively. Daning-Poleg et al (2001) Monforte et al (2003) detected 6.3 alleles on 27 wild and cultivated melons, which was similar to the mean number of allele for reference genotypes in our study (6.55). This high value was due to various subspecies of melons which they examined.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The mean number of allele and effective alleles for SSR loci for the 24 Iranian accessions were 4.11 and 2.38, respectively. Daning-Poleg et al (2001) Monforte et al (2003) detected 6.3 alleles on 27 wild and cultivated melons, which was similar to the mean number of allele for reference genotypes in our study (6.55). This high value was due to various subspecies of melons which they examined.…”
Section: Discussionsupporting
confidence: 91%
“…This high value was due to various subspecies of melons which they examined. The percentage of gene loci polymorphism that Katzir et al (1996) obtained using seven SSR primers on eight genotypes was 71 %, while Monforte et al (2003) found 100 % polymorphism, which was similar to our results. The difference between number of alleles in each locus and number of effective loci obtained herein shows the existence of rare alleles (alleles which have low frequency), so we can use these alleles to identify the Iranian melon genotypes by combination of some genetic loci.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Restriction Fragment Lengh Polymorphisms (RFLPs) (Neuhausen, 1992;Silberstein et al, 1999), Random Amplified Polymorphic DNA (RAPDs) (García et al, 1998;Stepansky et al, 1999;Silberstein et al, 1999;Staub et al, 2000;Zhuang et al, 2004), Amplified Fragment Lengh Polymorphisms (AFLPs) (Garcia-Mas et al, 2000), microsatellites or Simple Sequence Repeats (SSRs) (Katzir et al, 1996;Staub et al, 2000;Danin-Poleg et al, 2001;Mliki et al, 2001;Monforte et al, 2003;Zhuang et al, 2004), Internal Simple Sequence Repeats (ISSRs) (Stepansky et al, 1999) and the sequence and structural analysis of the Internal Transcribed Spacer (ITS) (Fantaccione et al, 2008). In general, similar clustering is obtained with the different types of…”
Section: I21 Genus Cucumismentioning
confidence: 99%